Revolusi Kurikulum di UPT SD Negeri 060861: Membangun Generasi Cerdas dan Berkarakter - Siagian, Amalia Alfina BR; A, Aufa; Rahmadi, Ihsan; Manjuntak, Miftah Hayati; Berutu, Sabila Meliani; Siagian, Zaura Izzati (Madani: Jurnal Ilmiah Multidisiplin, 2024)
In an effort to build the quality of education, one of the important components is the curriculum. The curriculum is seen as a plan prepared to facilitate the teaching and learning process under the guidance and responsibility of the school or educational institution and its teaching staff. The curriculum often undergoes changes or changes with the government's reason for changing the curriculum is to perfect and achieve curriculum goals that could not be achieved in the previous curriculum. The approach used in this research is a qualitative approach which is used to find out or describe the reality of the events being studied so as to make it easier to obtain objective data. The results and discussion of this research are that readers can find out what are the prominent differences between the K13 curriculum and the Merdeka curriculum, and readers can also find out how the process of character formation for students at SDN 060861 takes place in the current curriculum.